LALPUR: A MICROLITHIC SITE ADJACENT TO THE INDIRA GANDHI NATIONAL TRIBAL UNIVERSITY, AMARKANTAK, MADHYA PRADESH, INDIA - B. Janardhana (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2020)
In Indian Subcontinent the Microblade technology is continuously present from the late Middle Palaeolithic until the Iron Age period, making its association with modern humans very much undisputed. This technology appears to lead to microblade manufacture, with fullblown microlithic appearing later. It is a well-known fact in the prehistory branch that microblade technology in the Indian Subcontinent was developed locally by modern humans after 35 ka. This paper demonstrates and discusses the Microlithic site discovered during a recent survey carried out by the author in the village of Lalpur situated adjacent to the Indira Gandhi National Tribal University, Amarkantak, Madhya Pradesh, India. Until a few years ago almost nothing was known of the Microlithic site in this region, even though several sites had already been discovered in the eastern state of Madhya Pradesh, India, which has always been known for its rich microlithic collections. It should be noted that over 600 sites have been reported to this date, containing some with tools for tasks bound for heavy-duty.